NUTRITIONAL ANALYSIS, TOTAL PHENOLIC CONTENT, FREE RADICAL SCAVENGING ACTIVITY AND PHYTOCHEMICAL ANALYSIS OF LEAVES POWDER OF MORINGA OLEIFERA (DRUMSTICK) AND CICER ARIETINUM (CHICK PEA) - ABHIJEET A. GATADE,; RAHUL C. RANVEER,; AKSHAYA K. SAHOO, (International Journal of Pharma and Bio Sciences, 2013)
This study aims to determine nutritional as well as medicinal properties of Moringa oleifera (Drumstick) and Cicer arietinum (Chick pea) leaves. The possible health benefits of these underutilized leafy vegetables were explored by determining total phenolic content by Folin-Ciocalteau reagent, free radical-scavenging activity by 2, 2-diphenyl-1-picrylhydrazyl and phytochemicals extracted with acetone, chloroform, petroleum ether and ethanol by GC-MS screening. The M. oleifera and C. arietinum leaves powders were good source of protein, crude fiber, vitamin C and total minerals, particularly calcium, phosphorus and iron. Total phenolic content of drumstick and chick pea leaves was 260 mg/g and 190 mg/g, whereas free radical scavenging activity was 36.06 and 80.12 µg/ml respectively. Major phytochemicals identified in both leaves were hexadecanoic acid, pentacosane, β-sitosterol, phytol, octadecatrienoic acid methyl ester and vitamin E acetate. All the compounds identified by GC-MS were medicinally valuable for the treatment of various human ailments.